2011
DOI: 10.1007/s10719-011-9364-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Fc N-glycan profiling in patients with gastric cancer by LC-ESI-MS: relation to tumor progression and survival

Abstract: The IgG Fc glycans strongly influence the Fcγ receptor interactions and Fc-mediated effector mechanisms. Changes in the structure of IgG glycans are associated with various diseases, such as infections and autoimmunity. However, the possible role of Fc glycans in tumor immunity is not yet fully understood. The aim of this study was to profile the Fc N-glycans of IgG samples from patients with gastric cancer (n = 80) and controls (n = 51) using LC-ESI-MS method to correlate the findings with stage of cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 48 publications
11
75
3
Order By: Relevance
“…Notable alterations in glycosylation of the IgG-Fc region have been described not only in autoimmune disorders but also in some malignancy diseases (16). For example, Chen et al (22) had reported that the changes in total IgG-Fc N-linked glycosylation was associated with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable alterations in glycosylation of the IgG-Fc region have been described not only in autoimmune disorders but also in some malignancy diseases (16). For example, Chen et al (22) had reported that the changes in total IgG-Fc N-linked glycosylation was associated with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced IgG-Fc galactosylation has been documented to be limited mainly to patients with certain inflammatory and autoimmune diseases, such as rheumatoid arthritis (RA) and Crohn's disease (12,13). Interestingly, higher levels of agalactosylated IgG oligosaccharides have recently been reported in patients with prostate cancer (14), ovarian cancer (15), and gastric cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to healthy individuals, there is a marked increase of agalactosylated and asialylated serum IgG in individuals with autoimmune diseases [51,[78][79][80][81], infectious diseases [81,82] and tumours [83,84]. It is still unclear whether the disease affects the glycosylation of all or just antigen-specific IgG, which then contribute to the overall change observed in total IgG.…”
Section: Igg Glycovariants Under Physiological and Patho-physiologicamentioning
confidence: 99%
“…Recently, glycosylation of IgG, which influences IgG effector function, has been reported to be associated with the prognosis of malignant tumors including pancreatic cancer [23,24]. This indicates that serum IgG of cancer patients may contain some autoantibodies associated with the disease progression, and autologous tumor can become a target of anti-tumor immune response in vivo.…”
Section: Discussionmentioning
confidence: 99%